Pengaruh Latihan Shadow Dan Shuttle Run Terhadap Footwork Olahraga Bulutangkis Usia 13 - 15 Tahun Pb Jaya Raya Jakarta - Febri Prasetyo Ari Wibowo; Novita; Asrori Yudhaprawira; Eskar Tri Denatara; Juli Candra (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
This research aims to find out the influence of shadow and shuttle run exercises on badminton sports footwork aged 13 - 15 years at PB Jaya Raya Jakarta. It used experimental methods with two groups pre-test-post-test design.The population in the study was athletes of PB Jaya Raya Jakarta numbered 30 people.Sampling technique used purposive sampling, with criteria namely: (1) the list of attending the last two months of training was at least 75% (activeness following training), (2) the player was an athlete of PB Jaya Raya Jakarta, (3) aged 13-15 years, (4) male.Based on these criteria that meet the number of 20 athletes. Foot movement agility instruments used foot circuit test instruments.Data analysis was using the t test. Based on the results of the study, it can be concluded that: (1) There was an influence of shadow training on the footwork of badminton sports aged 13-15 years PB Jaya Raya Jakarta, with thitung 3,289 > ttabel 2,26and significance value of 0.009 < 0.05 with an influence of 9.55%.(2) There was the influence of shuttle run training on badminton footwork aged 13-15 years PB Jaya Raya Jakarta, with a thitung 4,155 > ttabel 2,26 and a significance value of 0.002 < 0.05 with an influence of 10.69%.(3) The shuttle run method is more effective for badminton sports footwork aged 13-15 years PB Jaya Raya Jakarta than shadow method with an average post-test difference of 0.2619.